Network‐regulated organ allometry: The developmental regulation of morphological scaling. (21st June 2020) - Vea, Isabelle M.; Shingleton, Alexander W.
Abstract: Morphological scaling relationships, or allometries, describe how traits grow coordinately and covary among individuals in a population. The developmental regulation of scaling is essential to generate correctly proportioned adults across a range of body sizes, while the mis‐regulation of scaling may result in congenital birth defects. Research over several decades has identified the developmental mechanisms that regulate the size of individual traits. Nevertheless, we still have poor understanding of how these mechanisms work together to generate correlated size variation among traits in response to environmental and genetic variation. Conceptually, morphological scaling can be generated by size‐regulatory factors that act directly on multiple growing traits (trait‐autonomous scaling), or indirectly via hormones produced by central endocrine organs (systemically regulated scaling), and there are a number of well‐established examples of such mechanisms. There is much less evidence, however, that genetic and environmental variation actually acts on these mechanisms to generate morphological scaling in natural populations. More recent studies indicate that growing organs can themselves regulate the growth of other organs in the body. This suggests that covariation in trait size can be generated by network‐regulated scaling mechanisms that respond to changes in the growth of individual traits. Testing this hypothesis, and one of the main challenges of understanding morphological scaling, requires connecting mechanisms elucidated in the laboratory with patterns of scaling observed in the natural world. This article is categorized under: Establishment of Spatial and Temporal Patterns > Regulation of Size, Proportion, and Timing Comparative Development and Evolution > Organ System Comparisons Between Species Abstract : Morphological scaling describes how traits grow coordinately and covary among individuals in a population. Relative trait size can change by a shift in scaling slope or intercept, generating different body proportions. Environmental and genetic variation ( V ), systemic factors ( S ), and trait‐autonomous mechanisms work together to regulate morphological scaling.